Nocturnal migrants do not incur higher collision risk at wind turbines than diurnally active species. (2nd February 2017) - Welcker, Jorg; Liesenjohann, Monique; Blew, Jan; Nehls, Georg; Grünkorn, Thomas
Abstract : Nocturnally migrating birds, particularly passerines, are known to be vulnerable to collision with man‐made structures such as buildings, towers or offshore platforms, yet information with respect to wind farms is ambiguous. We recorded bird flight intensities using radar during autumn migration at four wind farms situated within a major migration flyway in northern Germany and simultaneously conducted systematic searches for collision fatalities at the same sites. We found that migration traffic rates at rotor height estimated by radar observations were significantly higher during the night, yet strictly nocturnal migrants constituted only 8.6% of all fatalities at the wind farms. In contrast to the situation at other vertical structures, nocturnal migrants do not have a higher risk of collision with wind energy facilities than do diurnally active species, but rather appear to circumvent collision more effectively.